2019
DOI: 10.3390/rel10020109
|View full text |Cite
|
Sign up to set email alerts
|

Religious Heterogamy and the Intergenerational Transmission of Religion: A Cross-National Analysis

Abstract: This study examines the effect of religious heterogamy on the transmission of religion from one generation to the next. Using data from 37 countries in the 2008 Religion III Module of the International Social Survey Programme (ISSP), I conduct a cross-national analysis of the relationship between parents’ religious heterogamy and their adult childrens’ religious lives. By estimating fixed effects regression models, I adjust for national-level confounders to examine patterns of association between having interr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 65 publications
0
14
0
Order By: Relevance
“…Lower rates of religious belonging among Generation 2.5 may be a result of the fact that a couple with one native and one immigrant partner have to make a more conscious decision about national church membership and what religion, if any, to raise their child in. Furthermore, Generation 2.5 may be more likely to have been raised by interreligious parents, following the notion that religion is less likely to be transmitted in a household with religiously heterogamous parents (McPhail, 2019). Given their openness to marrying someone from a different background, the immigrant parent in such a couple may also be more integrated and, as such, more secular (Carol, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Lower rates of religious belonging among Generation 2.5 may be a result of the fact that a couple with one native and one immigrant partner have to make a more conscious decision about national church membership and what religion, if any, to raise their child in. Furthermore, Generation 2.5 may be more likely to have been raised by interreligious parents, following the notion that religion is less likely to be transmitted in a household with religiously heterogamous parents (McPhail, 2019). Given their openness to marrying someone from a different background, the immigrant parent in such a couple may also be more integrated and, as such, more secular (Carol, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies on religious heterogamy of parents have found lower levels of religiosity among adult children of parents with diverse religious identities (Bengtson, 2013;McPhail, 2019;Myers, 1996). McPhail (2019) notes that religiously heterogamous parents have lower levels of religious commitment themselves and are less likely to involve their child in active religious practice in their home or in a religious community.…”
Section: Religious Socialization and Social Integrationmentioning
confidence: 99%
See 3 more Smart Citations